The impact of institutions on Firms' rejuvenation policies: Early retirement with severance pay versus simple Lay-Off. A cross-European analysis - Justina A. V. Fischer (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2010)
Early retirement of workers is used by firms as means to rejuvenate their workforces. In principle, workers can either simply be laid off or can be offered an early retirement option combined with a financial bonus. However, dismissing masses of older workers may be detrimental to social peace and stability and damage the firm's reputation, while entry into early retirement with a severance pay at least maintains the semblance of a worker's voluntary decision. Cross-national analyses of this topic using micro data are, however, widely missing. Using the SHARE (Survey of Health, Aging and Retirement in Europe) data set, this paper fills this gap by investigating to what extent institutional factors such as the generosity of the pension system and strong unions influence firms' rejuvenation policies. Stronger unions appear to lead to a higher likelihood of receiving a severance pay, as does a more generous pension system. In contrast, a higher decrease in wealth accrual leads to a higher probability of simple lay-off. It is concluded that the current reforms which aim at lowering the replacement rate and employment protection will most probably lead to more dismissals of older workers without severance pay.
Keywords: J14; J21; J22; J26; 330; Early Retirement; Involuntary Early Retirement; Severance Pay; Social Security; Pensions; Employment Protection; Unions